A Systematic Review on Feline Internal Medicine Articles of Indonesian Veterinary Journals - Handoko, Jully; Paryuni, Alsi Dara; Pratama, Hadimas Bakti; Sari, Sayu Raka Padma Wulan (Universitas Airlangga, 2025)
This systematic review assesses the diversity of research approaches and methodologies in feline internal medicine articles published by Indonesian veterinary journals between 2012 and 2024. Content analysis was conducted on 20 veterinary journals from veterinary schools across Indonesia, with 17 journals (85%) featuring a total of 123 articles on feline internal medicine. A notable increase in articles was observed from 2017, peaking in 2023 with 35 articles (28.46%). Quantitative methods were the most commonly used in 48 articles (39.02%), followed by mixed methods in 44 articles (35.77%) and qualitative approaches in 31 articles (25.20%). Case reports were the predominant research design, found in 65 articles (52.85%), followed by cross-sectional studies (21.14%) and surveys (14.63%). Other designs included RCTs, laboratory studies, case-control, reviews, and cohort studies. Data collection techniques primarily involved testing (82.11%), with additional methods like document analysis, observation, and testing combined with interviews. Descriptive analysis was employed in 106 articles (86.18%), followed by Chi-square (5.69%) and t-test (2.44%). Infectious diseases were the focus of 67 articles (54.47%), while 44 articles (35.77%) addressed non-infectious diseases, and 12 articles (9.76%) covered other topics. The findings indicate a growing interest and methodological diversity in feline internal medicine research within Indonesia.